Long-term Potentiation Decay and Poor Long-lasting Memory Process in the Wild Rodents Proechimys from Brazil’s Amazon Rainforest - Guimarães Marques, Marcia J.; Reyes-Garcia, Selvin Z.; Marques-Carneiro, José E.; Lopes-Silva, Leonardo B.; Andersen, Monica L.; Cavalheiro, Esper A.; Scorza, Fulvio A.; Scorza, Carla A. (Frontiers in Behavioral Neuroscience, 2018)
Proechimys are small terrestrial rodents from Amazon rainforest. Each animal species is adapted to a specific environment in which the animal evolved therefore without comparative approaches unique characteristics of distinct species cannot be fully recognized. Laboratory rodents are exceedingly inbred strains dissociated from their native habitats and their fundamental ecological aspects are abstracted. Thus, the employment of exotic non-model species can be informative and complement conventional animal models. With the aim of promoting comparative studies between the exotic wildlife populations in the laboratory and traditional rodent model, we surveyed a type of synaptic plasticity intimately related to memory encoding in animals. Using theta-burst paradigm, in vitro long-term potentiation (LTP) in the CA1 subfield of hippocampal slices was assessed in the Amazon rodents Proechimys and Wistar rats. Memory, learning and anxiety were investigated through the plus-maze discriminative avoidance task (PM-DAT) and object recognition test. In PM-DAT, both animal species were submitted to two test sessions (3-h and 24-h) after the conditioning training. Proechimys exhibited higher anxiety-like behavior in the training session but during test sessions both species exhibited similar patterns of anxiety-related behavior. After 3-h of the training, Proechimys and Wistar spent significantly less time in the aversive enclosed arm than in the non-aversive arm. But, at 24-h after training, Wistar rats remained less time in the aversive closed arm in comparison with the non-aversive one, while Proechimys rodents spent the same amount of time in both enclosed arms. In the object recognition test, both species were evaluated at 24-h after the acquisition session and similar findings than those of the PM-DAT (24-h) were obtained, suggesting that long-term memory duration did not persist for 24-h in the Amazon rodent. Field excitatory post-synaptic potentials recordings revealed that LTP decays rapidly over time reaching basal levels at 90 min after theta-burst stimulation in Proechimys, contrasting to the stable LTP found in the Wistar rats which was observed throughout 3-h recording period. These findings suggest a link between the LTP decay and the lack of 24-h long-lasting memory process in Proechimys. Nevertheless, why early-phase LTP in Proechimys decays very rapidly remains to be elucidated.